2019
DOI: 10.1007/s13224-018-1191-8
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Versus Oral Iron for Treatment of Iron Deficiency Anaemia During Pregnancy and post-partum: A Systematic Review

Abstract: Introduction The burden of iron deficiency anaemia during pregnancy and post-partum continues to remain high especially in India. Challenges to treatment include gastrointestinal side effects and non compliance to oral iron therapy. Newer parenteral formulations need to be explored as alternatives. Methods Meta-analysis of randomized controlled trials published between years 2011 and 2018 comparing anaemic pregnant and post-partum women treated with intravenous iron sucrose versus oral iron was performed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 37 publications
5
21
0
3
Order By: Relevance
“…52 In second and third trimesters, IV iron therapy is safe and generally favored over oral formulations due to fewer side effects and rapid correction of anemia. 53,54 Ferric carboxymaltose is commonly used when treating second and third-trimester pregnancy IDA given its comparable safety profile to iron sucrose while requiring fewer repeated applications due to higher iron dose with each administration. [55][56][57] Since hypophosphatemia is a known side effect of ferric carboxymaltose, care should be taken to mitigate any exacerbating factors like vitamin D deficiency.…”
Section: Iron Defi Cien C Y Anemia In Preg Nan C Ymentioning
confidence: 99%
“…52 In second and third trimesters, IV iron therapy is safe and generally favored over oral formulations due to fewer side effects and rapid correction of anemia. 53,54 Ferric carboxymaltose is commonly used when treating second and third-trimester pregnancy IDA given its comparable safety profile to iron sucrose while requiring fewer repeated applications due to higher iron dose with each administration. [55][56][57] Since hypophosphatemia is a known side effect of ferric carboxymaltose, care should be taken to mitigate any exacerbating factors like vitamin D deficiency.…”
Section: Iron Defi Cien C Y Anemia In Preg Nan C Ymentioning
confidence: 99%
“…The existing evidence argues the efficacy of parenteral iron compared to the oral iron in the management of mild to moderate anemia and this is faster and more effective at restoring hemoglobin and total body iron deficits compared to oral iron, and has the added advantage of avoiding gastrointestinal side effects which often interrupt the treatment compliance in the postnatal women (Bhandal and Russell, 2006;Ehrenstein et al, 2006;Radhika et al, 2019;Sultan et al, 2019;Van Wyck et al, 2007). However, due to excellent safety and tolerance profile as well as easy availability at a cheaper price IV iron (iron sucrose) could be an appropriate alternative to blood transfusions in hemodynamically stable moderate to severely anemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite multiple existing evidences on comparison between IV and oral iron preparations (Bhandal and Russell, 2006;Ehrenstein et al, 2006;Radhika et al, 2019;Sultan et al, 2019;Van Wyck et al, 2007), there is a substantial lack in comparative study on effectiveness of IV iron sucrose with blood transfusion. A study conducted among anemic postpartum women of Saudi Arabia reported similar rise in Hb level after six weeks of intervention in both IV iron sucrose (2.15 g/dl) and blood transfusion group (2.35 g/dl) though the mean rise in ferritin level was higher in IV iron sucrose group (220%) than blood transfusion group (150%) (Khamaiseh and Tahat, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although oral iron treatment is often adequate, it is complicated by gastrointestinal adverse effects, which may limit its acceptability 3 . Intravenous iron is indicated in patients intolerant to oral iron or in whom oral iron has been ineffective, and restores iron stores and raises haemoglobin more rapidly than oral therapy 4–7 . Ferric carboxymaltose (FCM), along with iron isomaltoside and ferumoxytol, is one of the new‐generation iron‐carbohydrate formulations that can provide total dose iron replacement over 1−2 infusions.…”
Section: Introductionmentioning
confidence: 99%
“…3 Intravenous iron is indicated in patients intolerant to oral iron or in whom oral iron has been ineffective, and restores iron stores and raises haemoglobin more rapidly than oral therapy. [4][5][6][7] Ferric carboxymaltose (FCM), along with iron isomaltoside and ferumoxytol, is one of the new-generation iron-carbohydrate formulations that can provide total dose iron replacement over 1−2 infusions. FCM has been approved for intravenous administration of up to 1000 mg of iron in a single infusion, diluted in up to 250 mL saline and given over 15 min.…”
Section: Introductionmentioning
confidence: 99%